APPLICATION OF THE DRILL AND PRACTICE METHOD IN IMPROVING THE WRITING ABILITY OF JAVANESE CHARACTER STUDENTS IN CLASS VIIIB OF SMP NEGERI 36 SEMARANG ACADEMIC YEAR 2023/2024 - Riyandanti, Dian Lestari; Windaryati, Woro Endah Sri; Fuadhiyah, Ucik Fuadhiyah (Universitas PGRI Semarang, 2025)
This research was motivated by the low percentage of students' completeness in writing Javanese script skills in class VIII B of SMP Negeri 36 Semarang. The factors that cause students' low level of mastery in writing Javanese script are the use of learning methods that are still conventional so that the center of learning is the teacher which causes students to become less active, in addition to the students' view that Javanese script material is material that is very difficult to learn. This research is a type of classroom action research (PTK). The data obtained in this research was collected using tests and non-tests. Tests are given to measure students' cognitive abilities, while non-tests are used as supporting data which is carried out by means of observation, interviews and documentation. The data analysis technique used in this research is quantitative description. Quantitative data analysis techniques were used to analyze the results of the Javanese script writing skills test in the form of students' mastery scores which were analyzed using descriptive statistics. Based on the data obtained, the initial condition at the time of giving the pre-test was that only 7 or 22,59% of students had completed writing skills. After being given treatment using the Drill and Practice method, students' writing skills improved, from the first cycle test to the post test in cycle two, they continued to show improvement. The final results of the second cycle post test showed that there were 23 or 74.19% of students who had completed Javanese script writing skills. Thus, it can be said that the Drill and Practice method contributes to efforts to improve Javanese script writing skills in class VIII B of SMP Negeri 36 Semarang.